Terapia comunitária integrativa e família na perspectiva sistêmica novo - paradigmática: convivendo com o sofrimento psíquico - Carvalho, Mariana Albernaz Pinheiro de (2018)
INTRODUCTION: The ICT is defined as an advanced psychosocial intervention that is organized as a community space capable of exchanging experiences and life stories. Working in a horizontal and circular way, it proposes co-responsibility in a therapeutic process that generates individual and group repercussions. It is one more resource to be used by the professional of Basic Attention, especially by the nurse, with relatives who live with the reality of the psychic suffering. Objective: To evaluate the efficacy of ICT as a psychosocial intervention capable of enhancing self-esteem, minimizing overload levels and reestablishing links between family caregivers of relatives using CAPS, aiming to strengthen relationships in the family system. Method: Research of qualitative approach that used the method of research-action-intervention. The intervention used was 12 ICT wheels in 4 months. The study included 10 relatives of people in psychic suffering accompanied at a Psychosocial Care Center of the city of João Pessoa - Paraíba, who participated in at least 6 ICT wheels. To obtain the empirical material, we used the family overload rating scale, the tool for evaluation of the links and the self-esteem evaluation tool created by Barreto. As techniques of production of the empirical material, the records and impressions pointed out in the field book, the videos obtained with the recording of the ICT wheel, the material obtained through the interviews, besides the ICT itself, were used. The research obeyed the ethical principles governed by Resolution 466/12 and was carried out with the approval of the Research Ethics Committee, after issuing the Certificate of Presentation for Ethical Appreciation nº 55962216.0.0000.5188. Results: The research revealed that 90% of the participants presented an increase in self-esteem levels, 70% showed a growth in the number of ties and all the family members reduced the overload scores in at least two dimensions of the FBIS-BR scale. The study also revealed that family members understanding of psychic suffering could be transformed by the step that they attributed new meanings and made actions and choices fundamental to the balanced living of the family and the relationships established there. Conclusion: The ICT could be elucidated as a practice that facilitated changes in the personal, family and community spheres of the participants, as it contributed to reduce overload, increase self-esteem and strengthen ties, further on generate social and individual interactions that stimulated family members to rethink concepts and to create spaces of human and respectful coexistence and care that have spread to the family system.